2016
DOI: 10.3389/fpls.2016.01688
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure and Evolutionary History of Three Alpine Sclerophyllous Oaks in East Himalaya-Hengduan Mountains and Adjacent Regions

Abstract: The East Himalaya-Hengduan Mountains (EH-HM) region has a high biodiversity and harbors numerous endemic alpine plants. This is probably the result of combined orographic and climate oscillations occurring since late Tertiary. Here, we determined the genetic structure and evolutionary history of alpine oak species (including Quercus spinosa, Quercus aquifolioides, and Quercus rehderiana) using both cytoplasmic-nuclear markers and ecological niche models (ENMs), and elucidated the impacts of climate oscillation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 107 publications
(119 reference statements)
2
21
0
Order By: Relevance
“…In this study, various cp DNA haplotypes exist within a species and some of these haplotypes are shared interspecifically. Recent phylogeographic studies of the section Ilex from the Himalayas ( Feng et al, 2016 ; Meng et al, 2017 ) and the pan-Mediterranean ( Simeone et al, 2016 ; Vitelli et al, 2017 ) also showed similar scenario. Moreover, even using the complete plastid genome sequences for phylogenetic reconstruction, the monophyletic status of species was still rare in section Quercus ( Pham et al, 2017 ).…”
Section: Discussionmentioning
confidence: 69%
“…In this study, various cp DNA haplotypes exist within a species and some of these haplotypes are shared interspecifically. Recent phylogeographic studies of the section Ilex from the Himalayas ( Feng et al, 2016 ; Meng et al, 2017 ) and the pan-Mediterranean ( Simeone et al, 2016 ; Vitelli et al, 2017 ) also showed similar scenario. Moreover, even using the complete plastid genome sequences for phylogenetic reconstruction, the monophyletic status of species was still rare in section Quercus ( Pham et al, 2017 ).…”
Section: Discussionmentioning
confidence: 69%
“…The uplift of the Yunnan–Guizhou plateau in SW China likely occurred in the late Miocene–Pliocene (Clark et al, ; Favre et al, ), a period of global cooling and intensification of Asian monsoons. Habitat fragmentation caused by the Yunnan–Guizhou plateau uplift during Miocene–Pliocene may have fostered intraspecfic divergence in this region (Feng et al, ; He & Chen, ).…”
Section: Discussionmentioning
confidence: 99%
“…The program 2MOD v0.2 (Ciofi, Beaumontf, Swingland, & Bruford, 1999) was used to estimate the relative likelihoods of immigration-drift equilibrium and drift since a certain time (i.e., the relative effects of gene flow and genetic drift in the current population structure). The program used the settings of Feng et al (2016), each model was run three times to check whether the MCMC had converged, 100,000 iterations were performed, and the first 10% of iterations in the output were excluded to avoid dependence on initial starting values.…”
Section: Bottlenecks and Formation Pattern Of Population Structurementioning
confidence: 99%